Specificity of Author’s Modality and Representation of Russia’s Image in Claudia Erdheim’s Book “Früher war alles besser”: an Austrian View - T. A. Sharypina; P. D. Kazakova; V. N. Egorova (Научный диалог)
The reception of a foreign cultural (Russian) code by the European (Austrian) literary consciousness on the problematic, stylistic and lexical levels are studied in the article. The main trend characteristic for the representation of the image of Russia in the book by Claudia Erdheim is revealed: a retrospective look into the “bright past”. It is emphasized that the refrain phrase “Früher war alles besser” in the title has a symbolic meaning. Five mini-stories were analyzed. Attention is paid to the stereotypes of the Russian mass consciousness. Political stereotypes, ethical canons are studied in the perception of the author-narrator. It is argued that the antinomy of the Western way of thinking and the Russian mentality is the prevailing motive in the work under study. It is proved that the problem of the Russian-Austrian cultural dialogue is realized through the prism of the fundamental components of the Austrian mentality Einfühlung (feeling) and Gemütlichkeit (comfort, tranquility). Among the mental clichés of the narrator, stereotyped ideas about the Russian character (“broad soul”, “Russian scope”, “Russian maybe”, “longing”) are found. The book by K. Erdheim is a vivid example of the representation of the “Other” / “Alien” ideas about the “Other” national character and recreates the image of the Russian people in its artistic system.